Cognitively diagnostic assessment - Nichols, Paul D. Etal (b)
During the past two or three decades, research in cognitive science and psychology has yielded an improved understanding of the fundamental psychological nature of knowledge and cognitive skills that psychological testing attempts to measure. These theories have reached sufficient maturity, making it reasonable to look upon them to provide a sound theoretical foundation for assessment, particulary for the content of assessments. This fact, combined with much discontentedness over current testing practices, has inspired efforts to bring testing and cognitive theory together to create a new theo
include reference and index
Keywords: Cognition -- Testing -- Congresses..; Psychometrics -- Congresses